A proxy for atmospheric daytime gaseous sulfuric acid concentration in urban Beijing - Y. Lu; C. Yan; Y. Fu; Y. Chen; Y. Liu; G. Yang; Y. Wang; F. Bianchi; B. Chu; Y. Zhou; R. Yin; R. Baalbaki; et al. (Atmospheric Chemistry and Physics, 2019)
Gaseous sulfuric acid (H2SO4) is known as one of the key precursors for atmospheric new particle formation (NPF) processes, but its measurement remains challenging. Therefore, a proxy method that is able to derive gaseous sulfuric acid concentrations from parameters that can be measured relatively easily and accurately is highly desirable for the atmospheric chemistry community. Although such methods are available for clean atmospheric environments, a proxy that works well in a polluted atmosphere, such as that found in Chinese megacities, is yet to be developed. In this study, the gaseous sulfuric acid concentration was measured in February–March 2018, in urban Beijing using a nitrate based – long time-of-flight chemical ionization mass spectrometer (LToF-CIMS). A number of atmospheric parameters were recorded concurrently including the ultraviolet radiation B (UVB) intensity, the concentrations of O3, NOx (sum of NO and NO2), SO2, and HONO, and aerosol particle number size distributions. A proxy for atmospheric daytime gaseous sulfuric acid concentration was derived via a statistical analysis method using the UVB intensity, [SO2], the condensation sink (CS), [O3], and [HONO] (or [NOx]) as the predictor variables, where square brackets denote the concentrations of the corresponding species. In this proxy method, we considered the formation of gaseous sulfuric acid from reactions of SO2 and OH radicals during the daytime, and the loss of gaseous sulfuric acid due to its condensation onto the preexisting particles. In addition, we explored the formation of OH radicals from the conventional gas-phase photochemistry using O3 as a proxy and from the photolysis of HONO using HONO (and subsequently NOx) as a proxy. Our results showed that the UVB intensity and [SO2] are dominant factors in the production of gaseous sulfuric acid, and that the simplest proxy could be constructed with the UVB intensity and [SO2] alone. When the OH radical production from both homogenously and heterogeneously formed precursors were considered, the relative errors were reduced by up to 20 %.